THE MODERN VIEW ON THE PROBLEM OF TREATMENT OF CHRONIC HEPATITIS B DURING PREGNANCY - L. O. Makarov; Ch. S. Pavlov; T. V. Shemaneva; S. M. Voevodin; A. Yu. Muravey (Акушерство, гинекология и репродукция)
The pregnancy outcome depends on a stage of a current of disease by a virus hepatitis. The factors defining the forecast of disease at chronic virus hepatitises, activity of inflammatory process and intensity of formation fibrosis in a liver which can be estimated a noninvasive method is.